Numerical study of atmospheric ice accretion on rotating geometric cross sections with fins. (March 2016) - Mughal, Umair N; Virk, Muhammad S
This paper describes the numerical study of atmospheric ice accretion on rotating geometric cross sections, circular, hexagon and square, all having fins, to select an optimum geometric cross section for use as a rotating part of a newly-proposed designed icing sensor. Computational fluid dynamics-based numerical analyses were carried out in this research work to understand and analyse the atmospheric ice growth on these rotating cross sections at varying operating and geometric parameters. A comparison of accreted ice profile shapes from numerical analysis was also made with the experiments, carried out at cryospheric environment simulator (CES), Shinjo Japan. A good agreement was found between numerical and experimental results.